Development and characterization of alginate microspheres containing tolcapone by ionotropic gelation method - Suggala Ajay; G. Ganesh; Gande Suresh (International Journal of Pharmacy and Analytical Research, 2022)
The present study was designed to formulate and evaluate the Tolcapone sodium alginate microspheres. Fourteen formulations batches of microspheres (S1 -S14) were prepared by using ionotropic gelation method . Sodium alginate, calcium chloride and gelatin wer e selected in the formulations. The effect of polymer and cross-linking agent on particle size, shape, % yield, entrapment efficiency, and drug release were studied. From the evaluation parameters S13 was found to be optimized and the drug release was high est of 97.55% with in 12 h in controlled manner when compared with other parameters. From release order kinetics the drug release from microspheres was followed zero order with anomalous Non fickian diffusion. The prepared microspheres were further preceded for compatibility studies and morphological studies, found to be compatible with the polymers. Thus, Tolcapone microspheres could be the best choice in the effective management of Parkinsonism with better patient compliance for prolonged period of time.